Break Time: A SWOT Analysis for an Order Management System for Food Court in Universities and Colleges - Zheng Xiong, Tan; Che Abdul Rani, Mohamad Firdaus; Shajaratuddur Harun, Khalida (International Journal of Psychosocial Rehabilitation, 2019)
Food court in universities and colleges, is often the go-to spot for the students and staffs either for meals, quick bites, or even a place to relax. With the increasing number of staffs and students, the food court has quickly become very congested especially during peak hours such as lunch. Occasionally, long queues can still be found even the food court is not at its peak hours. This is not a good sign as it will cause more customers to be impatient, and more challenges arise to the food court. BreakTime is introduced to improve the situation for food court in universities and colleges. The proposed web-based system will be used by three different users; System Administrator, Food Court Stall’s Representative and Customers. This paper identifies strengths, weaknesses, opportunities and threats that could potentially impact the success of BreakTime and analyses common situations happening in the universities’ or colleges’ food court and to identify value added features for BreakTime.